SEMINAR MENGENAI PROSES PEMBUATAN SPARE PARTS OTOMOTIF MELALUI PROSES DIE CASTING PADA SISWA SMK KARYA GUNA 1 BEKASI - Joko Sri Widodo; Taufiqur Rokhman; R. Hengki Rahmanto (An-Nizam, 2022)
Currently in the manufacturing and automotive industries, the use of metal and aluminum materials is experiencing rapid development. The use of metal materials is very diverse, in the automotive industry it is usually used for the process of making spare parts on motorcycles and cars. One of the processes of utilizing metal materials to be used as spare parts for automotive vehicles is through the Die Casting process. Metal casting with the Die Casting process is a casting method by injecting molten metal into a mold with a certain speed and pressure using a Die Casting machine, so that it will form a product according to the mold. Current Condition of the Covid-19 pandemic, it is very difficult for the general public, especially students, to know about the Die Casting process in Industry which can usually be obtained through industrial visits, because during a pandemic there must be restrictions. Therefore, giving knowledge of the die casting process to students is very useful in this conditions.